Biodiversity in a Batak village of Palawan (Philippines): a multidisciplinary assessment of local perceptions and priorities - Boissiere, M.; Liswanti, N. (Center for International Forestry Research, 2006)
This report identifies which resources and landscapes are important to the Batak people. It also documents their perceptions and priorities regarding forest management. By playing close attention to the Bataks’ perspectives, the “Levelling the Playing Field” project (LPF) is able to better understand their opinions and hopes for the present and future use of their natural resources. Further, by understating local perceptions, greater insight is gained into the complex relations between the Bataks and coastal migrants living in the district capital (barangay), and their political and economic marginalization on Palawan Island.